Políticas públicas de ciência, tecnologia e inovaç\~ao: uma pesquisa empírica da lei de inovaç\~ao - Patricia Guimaraes; Yanko Xavier; Lucas do Monte Silva (European Regional Science Association (ERSA), 2015)
This paper aims to analyze, from a legal perspective, the public policies of Science, Technology and Innovation offered by the Brazilian government, more specifically, the Innovation Act (Lei de Inovaç\~ao), in order to verify the effectiveness and impact of this measure for development, in the Brazilian entrepreneurial scene. Through empirical research and comparative method, this research seeks to answer, preliminarily, the following questions: a) What is innovation? b) The State should act in the innovation process?; c) What is the relationship beetween innovation and development?; d) What are the aspects of public policies of Science, Technology and Innovation offered by the Brazilian government made available to entrepreneurs in the Innovation Law? What is the effectiveness and impact of this measure in the Brazilian entrepreneurial scenario? The questioning of the article was analyzed based on the premise that innovation is essential to the development of a society and its economy. Innovation is not only limited to radical ruptures, such as the introduction of smart watches or autonomous cars, but it also covers moderate advances, such as new product specific production methods, new ways of customer service or (re)configuration of bureaucratic procedures in order to speed them up. Thus, innovation is presented from the need to solve problems that citizens, whether entrepreneurs or not, appears in any given moment. An innovative society tends to have a higher quality of life, higher productivity and, consequently, the factors for the nation?s economic growth in which it resides. It turns out that in developing countries, the private sector, that is, entrepreneurs, don't always have the resources, opportunity, know-how and structure to take the risk of investments in Research, Development and Innovation (RD&I) as assumed initially by Schumpeter. These entrepreneurs prefer to license technology from foreign nations or larger companies, which have been tested and proven, rather than take the risk of spending millions of dollars on products, services, innovative processes that do not have the expected profit, or even, doesn't go beyond a mere prototype. Thus, as highlighted by neo-schumpeterians economists, the State presents itself as a key player in these countries, since it has conditions, financial and technical, to stimulate, either through direct measurements, either through indirect measures, innovation. We concluded that Brazil presents advances in this sector and most of public policies managed to have efficacy for entrepreneurs, but it is also necessary institutional changes in the process of receiving these incentives and in its supervision, improving them, so that companies incubated may have the same competitivety of foreign companies.
Keywords: L5; N46; O1; 330; institutionalism; law and development; innovation